1993
DOI: 10.1243/pime_proc_1993_207_194_02
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Development of the LotusSport Pursuit Bicycle

Abstract: Aerodynamic drag constitutes over 96 per cent of the overall resistance to motion for a typical rider and bicycle combination. Although the rider of a typical track pursuit bicycle constitutes approximately two-thirds of the overall aerodynamic drag, the bicycle itseEf still contributes one-third. Any reduction in the drag generated by the bicyclr can therefore have a signijicant effect on the maximum attainable speed for a given power input, and thus the time to cover a given race distance. At the same time i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A clear distinction in upright vs. time-trial ensemble average drag area is found for both experiments, with the upright posture yielding higher drag area by about 20-35% with respect to the time-trial posture. Kyle (1991), 2 Hill (1993), 3 Broker andKyle (1995), 4 Zdravkovic et al (1996), 5 Martin et al (1998), 6 Padilla et al (2000, 7 Jeukendrup and Martin (2001), 8 Gibertini and Grassi (2008), 9 Garcia-Lopez et al 2008 Grappe et al (1997), 24 Candau et al (1999), 25 Peterman et al (2015), 26 Nonweiler (1958, 27 Kyle and Burke (1984), 28 Fintelman et al 2014, 29 Capelli et al (1993), 30 de Groot et al (1995, 31 Lim et al (2011)…”
Section: Discussionmentioning
confidence: 99%
“…A clear distinction in upright vs. time-trial ensemble average drag area is found for both experiments, with the upright posture yielding higher drag area by about 20-35% with respect to the time-trial posture. Kyle (1991), 2 Hill (1993), 3 Broker andKyle (1995), 4 Zdravkovic et al (1996), 5 Martin et al (1998), 6 Padilla et al (2000, 7 Jeukendrup and Martin (2001), 8 Gibertini and Grassi (2008), 9 Garcia-Lopez et al 2008 Grappe et al (1997), 24 Candau et al (1999), 25 Peterman et al (2015), 26 Nonweiler (1958, 27 Kyle and Burke (1984), 28 Fintelman et al 2014, 29 Capelli et al (1993), 30 de Groot et al (1995, 31 Lim et al (2011)…”
Section: Discussionmentioning
confidence: 99%